2017
DOI: 10.1002/ijop.12465
|View full text |Cite
|
Sign up to set email alerts
|

Positive discipline, harsh physical discipline, physical discipline and psychological aggression in five Caribbean countries: Associations with preschoolers' early literacy skills

Abstract: Physical punishment has received worldwide attention because of its negative impact on children's cognitive and social development and its implications for children's rights. Using UNICEF Multiple Indicator Cluster Surveys 4 and 5 data, we assessed the associations between positive discipline, harsh physical punishment, physical punishment and psychological aggression and preschoolers' literacy skills in 5628 preschool-aged children and their caregivers in the developing nations of Belize, the Dominican Republ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(13 citation statements)
references
References 31 publications
0
11
0
2
Order By: Relevance
“…One psychological technique that is not very common in digital interventions (though it could be easily incorporated) is the presentation of an artificial step prior to a subsequent step that otherwise might demand too much effort to complete. For example, when parents are taught to present an appropriate nonharsh consequence in the event of their child's disobedience [48,49], this step may feel like a giant leap, thus demanding plenty of effort in the parents' mind. We may, therefore, create another step of setting expectations for which parents are directed to sit with their child prior to changing the way they react to them and to simply present the fact that they are going to do whatever they can to help them, meaning the rules of the house are going to change.…”
Section: Setting Graded and Dynamically Tailored Therapeutic Activitimentioning
confidence: 99%
“…One psychological technique that is not very common in digital interventions (though it could be easily incorporated) is the presentation of an artificial step prior to a subsequent step that otherwise might demand too much effort to complete. For example, when parents are taught to present an appropriate nonharsh consequence in the event of their child's disobedience [48,49], this step may feel like a giant leap, thus demanding plenty of effort in the parents' mind. We may, therefore, create another step of setting expectations for which parents are directed to sit with their child prior to changing the way they react to them and to simply present the fact that they are going to do whatever they can to help them, meaning the rules of the house are going to change.…”
Section: Setting Graded and Dynamically Tailored Therapeutic Activitimentioning
confidence: 99%
“…Other international studies have used MICS data to examine the association between spanking and child well-being have used smaller subsets of countries. For example, one study examined the prevalence of physical punishment in five Caribbean countries ( Yildirim & Roopnarine, 2017 ). Frongillo, Kulkarni, Basnet, and de Castro, (2017) examined physical punishment and child educational outcomes using data from 26 MICS countries ( Frongillo et al, 2017 ).…”
Section: Introductionmentioning
confidence: 99%
“…Finally, we found that caregivers who believed in physical punishment used more positive and also more negative discipline methods. Therefore, positive and negative discipline methods are not mutually exclusive, as has been shown earlier in Caribbean countries (52) , and a caregiver of a child with challenging behaviors might use multiple discipline strategies.…”
Section: Discussionmentioning
confidence: 83%